Antibacterial effects of Ceftriaxone/Zinc Oxide Nanoparticles Combination Against Ceftriaxone resistant Escherichia coli isolated from Urinary Tract Infections - Sarah F. Al-Taie; Dhafar N. Al-Ugaili; Khawla A. Kasar; Laith A. Yaaqoob (Indian Journal of Forensic Medicine & Toxicology, 2022)
This study was designed to shed light on the issue of pathogenic bacteria resistance to antibiotic, and to overcome it by taking the advantages of nanotechnology. A hundred and twenty urine samples were collected from patients of different ages and of both genders who showed symptoms of urinary tract infections, from three hospitals in Baghdad. Ceftriaxone E. coli was detected and isolated from these samples. More recently, nanotechnology application has grown in importance in this problem. In this study, we used Zinc oxide nanoparticle to enhance the activity of ceftriaxone. Zinc oxide nanoparticle (ZnO NP) was prepared by biological method of processing of a fresh leaf aloe vera plants. Further characterization methods, which are Fourier, transform infra-red Spectroscopy (FTIR), and Atomic Force Microscopy (AFM) (which showed that the average diameter of the newly created ZnO NP is 45.55 nm) were applied for checking the created nanoparticle. Antimicrobial ability of ZnO NP showed an inhibition zone with a 13 mm in diameter. The isolates of E. coli showed a resistance to ceftriaxone at a concentration of 100 μg/ml. The results of inhibition activity of ceftriaxone antibiotic against Escherichia coli isolates of the current study showed a remarkable change when mixed with ZnO NP, in which ceftriaxone became affective in inhibiting Escherichia coli growth.